Beyond Hegemony: How KNB Scholarship Program Redefines Indonesia’s Soft Power and Global South Knowledge Production - Gerale, Christopher Paller (Global South Review, 2025)
The Kemitraan Negara Berkembang (KNB) Scholarship Program, launched by the government of the Republic of Indonesia, represents a transformative approach to educational exchange that challenges traditional North-South paradigms. This study adopts several frameworks to comprehensively analyze how the KNB Scholarship Program fosters South-South Cooperation (SSC), disrupts Western-centric knowledge hierarchies, and contributes to capacity building in the Global South. Through a qualitative methodology, the research involves a comprehensive document review of official reports, policy papers, tracer studies, and university evaluations related to the scholarship program, as well as written and oral interviews from the current scholars and alumni and articles, theses, dissertations produced by KNB scholarship recipients. The findings highlight the KNB Scholarship’s role in redefining Indonesia’s soft power and reshaping Global South knowledge production. It serves not only as a means of individual empowerment but also as a catalyst for systemic change, which drives a transformation in the global educational and diplomatic landscape. In line with the Bandung Conference’s spirit of solidarity and self-determination, the KNB Scholarship Program advances Indonesia’s role in shaping a more inclusive and equitable global governance framework, offering valuable insights into the future of educational diplomacy and global power dynamics. By prioritizing Global South solidarity, equitable and sustainable development, and the decolonization of knowledge, the KNB Scholarship Program supports the objectives of promoting Indonesia’s soft power and governance in SSC and challenging the dominance of Western academic and political paradigms—which constitutes “KNB Diplomacy.”